2006
DOI: 10.1021/tx050336s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heparin on Viologen-Stimulated Enzymatic NADH Depletion

Abstract: Paraquat and diquat undergo redox cycling mediated by xanthine oxidase in the NADH-dependent manner. In these processes, the rates of NADH oxidation and superoxide formation are increased almost 10-fold. The addition of heparin can substantially inhibit these processes. A protective role of heparin against oxygen radicals formation can be rationalized in terms of its ability to bind paraquat or diquat. The binding process has been investigated by means of the pulse radiolysis technique. Biological consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…xanthine oxidase by decreasing and regulating the concentration of this enzyme which reduces the production of reactive oxygen species in the endothelium (18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…xanthine oxidase by decreasing and regulating the concentration of this enzyme which reduces the production of reactive oxygen species in the endothelium (18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…This makes it a highly polar divalent cationic compound that is easily reduced to an unstable DQ +● . 51 Further reduction yields polyhydrobipyridyl derivatives and atmospheric oxygen regenerates DQ 2+ . The distance between the two nitrogen atoms is about 3.5 Å.…”
Section: Physical and Chemical Properties And Formulationsmentioning
confidence: 99%
“…92 These metabolic pathways occur mainly in the liver via cytochrome P450 enzymes, and all metabolites are more easily excreted through the urine. 51,91,94 Fuke et al 35 identified both DQ dipyridone and monopyridone in the serum of three DQ-poisoned patients, with dipyridone reaching up to 20% of DQ in one patient. In vitro studies suggested that the cecal microflora of the rat can metabolize DQ to the monopyridone.…”
Section: Metabolismmentioning
confidence: 99%
See 2 more Smart Citations